PENGEMBANGAN MEREK DAN PENGKAJIAN STRATEGI PEMASARAN DI DEPOT RASA SUKA KEDIRI - Raharjo, Rini; Surjani, Rosita Meitha; Rinawiyanti, Esti Dwi (University of Surabaya, 2013)
Depot Rasa Suka is a culinary business that provides a variety of Indonesiandishes. However people still do not know and yet loyal to Depot Rasa Suka due tothe unavailability of parking space, quite a long serving time, hot room, lessattractive promotion and room design. Therefore Depot Rasa Suka need to devisestrategies to develop brands through brand equity analysis and improvement ofbrand elements as well as designing a marketing strategies. The goal of thisresearch is to make Depot Rasa Suka has a strong brand image and could meet thedesires of consumers based on consumer behavior to ensure that customers remainloyal and increase sales in Depot Rasa Suka. The research was conducted bydistributing questionnaire to the group of respondents that consists of actualconsumers and potential consumers. Based on the measurement of brand equity,brand equity scores for Depot Rasa Suka is 2 (medium). In order to enhance thebrand equity it is necessary to develop brand elements such as brand names orlogos, packaging, website, and marketing communications activities.Segmentation for Depot Rasa Suka is determined based on consumer behavioranalysis including demographics (age, marital status, education level, occupation,and income) and psychographics (knowledge, attitude, uses, occasions, benefitssought, usage rate, and loyalty status). The target market is aged 20-30 years old,self-employed occupations, average earnings per month Rp 3,000,000.00 -6,000,000.00 and spending per visit to the restaurant Rp 50,000.00 - 100,000.00.The positioning of Depot Rasa Suka is positioning according to quality and price.The differentiation of Depot Rasa Suka is product differentiation. Total cost in theproposed strategy is Rp 10,511,000.00.